The Relationship Between Functional Motor Status and Self-evaluation in Individuals with Cerebral Palsy: A Systematic Review - Roostaei, Meysam; Akbarfahimi, Nazila; Dalvand, Hamid; Abedi, Shiva (Iranian Journal of Child Neurology, 2021)
Abstract Cerebral palsy (CP) is a common pediatric disorder that results in a wide range of motor and functional problems that impose mobility limitations, decrease the quality of movement, negatively affect physical activity participation, self-care, and academic performance, and ultimately result in social isolation and negative self-evaluation. Despite abundant evidence of motor function, very few studies investigated all aspects of self-evaluation or described the relationship between motor function and self in individuals with CP. The present study aimed at investigating the relationship between functional motor status and self-evaluation in individuals with CP. A systematic search was performed in six electronic databases (PubMed, Scopus, ProQuest, OTseeker, Web of Sciences, and Google Scholar) for English language articles from any date to May 2019. Screening, selection, and quality assessment were conducted by two authors independently. All studies recruiting individuals with CP and using functional motor status and self-evaluation tests were included. The AXIS checklist was used for the quality assessment of included studies. As all data sources were generated by published studies, ethical approval was not applicable to the present study. Seven articles met the inclusion criteria. These studies investigated the relationship between functional motor status and self-esteem and selfconcept. Based on the AXIS, three articles were identified as high quality and four as low quality. The result of the present review showed that there was no relationship between self-concept and functional motor status in individuals with CP, while there was a significant relationship between self-esteem and functional motor status. More studies are required to shed light on other aspects of self and relationship of self-evaluation with motor function in individuals with CP.